2012
DOI: 10.1108/17542731211247373
|View full text |Cite
|
Sign up to set email alerts
|

Applying TQM to the construction industry

Abstract: Purpose-The purpose of this paper is to define the quality and productivity problems, and improvement opportunities that face the construction industry today. Design/methodology/approach-The authors conducted interviews and surveys plus they researched pertinent literature to come to their findings. Findings-The paper concludes that there is a lack of good research for improved approaches and that construction work is considered an undesirable profession. It also concludes that there has been a slow change ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
57
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(60 citation statements)
references
References 11 publications
0
57
0
3
Order By: Relevance
“…TQM are initiatives which enable organization's process improvement initiatives and this is due to inadequacies reported in their productivity or performance [2] [10] [11], business process management (BPR) [12] and etc.…”
Section: Defined Tqm As: "Total Quality Management Is the Combinationmentioning
confidence: 99%
See 1 more Smart Citation
“…TQM are initiatives which enable organization's process improvement initiatives and this is due to inadequacies reported in their productivity or performance [2] [10] [11], business process management (BPR) [12] and etc.…”
Section: Defined Tqm As: "Total Quality Management Is the Combinationmentioning
confidence: 99%
“…Another approach might be the introduction of TQM related programs in to the MBA and BBA degree programmes. Furthermore, a study conducted by Harrington et al [2] to investigate the productivity and quality problems and rooms for improvement found that there has been a slow variation over from quality control (QC) to TQM in construction industry.…”
Section: Defined Tqm As: "Total Quality Management Is the Combinationmentioning
confidence: 99%
“…Abundant literature suggests that public sector organisations with better communication systems have a better opportunity to deliver quality services (Nardi 2005;Hughes and Walters 2007;Garling 2008;Canary 2011;Jenkins et al 2011). Harrington et al (2012) affirm that communication is one of the most important organisations' strategic weapons that stimulate quality service delivery (QSD) as it strengthens employee relationships, permits conveyance of critical service delivery ideas to management, and eliminates fear that would have limited employee involvement in the QSD process. Local governments thus should find ways to strengthen their communication systems in order to cope with the challenges of QSD.…”
Section: Introductionmentioning
confidence: 98%
“…One way to achieve this is through communication (Harrington et al 2012). Although different approaches are used in the examination of communication construct, communication has been more recently considered from an organisational perspective as a pattern of information flow and exchange within the organisation (West and Turner 2007).…”
Section: Introductionmentioning
confidence: 99%
“…The competitive pressure forces construction firms to change their traditional methods in projects management with the aim of achieving the organizational goals successfully. This aim can be happened through the effective implementation of a "total quality management (TQM) system" (Harrington et al, 2012). TQM was first emerged by the contribution of quality gurus, such as Deming, Juran in Japan after Second World War.…”
Section: Introductionmentioning
confidence: 99%